Differentiated learning through the PBL model to improve Indonesian language learning outcomes for elementary school students - Solehudin Solehudin; Siti Rochmiyati (Universitas Kanjuruhan Malang, 2023)
One of the reasons for the low achievement of learning Indonesian in SDN 2 Tlogosari is the lack of attractiveness of students during learning. This study aims to determine the increase in student learning outcomes in the main idea material through differentiated learning with the Problem Based Learning (PBL) model. This type of research is classroom action research (CAR). The research subjects were grade 4 students at SDN 2 Tlogosari, Ayah District, Kebumen Regency. Data collection techniques using the methods of observation, interviews, and tests. The data obtained is then analyzed. The results of the research show that the implementation of differentiated learning in the PBL model can improve student learning outcomes in the main idea material.